1 - ANNE BOGART - Mele, Claudia; Lopes, Beth; Bonfitto, Matteo; Tornaghi, Transcription by Isabel (O Percevejo Online, 2011)
In this interview, Anne Bogart presents different aspects of her work with the SITI Company. The role of composition within the creative process is discussed and the function of interculturalism and interdisciplinarity in the work of the company is described. Anne Bogart talks of the close relationship that exists between her teaching and her artistic creation, and concludes the interview situating her work in a historical context. Keywords | Anne Bogart | improvisation | composition | interdisciplinarity | interculturalism ANNE BOGART earned a Bachelor of Arts degree from Bard College (1974), and a Master of Arts degree from New York University’s (1977). She is a Professor at Columbia University. She is the recipient of a Guggenheim Fellowship; two Obie Awards; the New York Dance and Performance Award (the Bessie Award); the Villager Award; and a National Endowment for the Arts Artistic Associate Grant. She has worked as artistic director of the Trinity Repertory Theater and co-artistic director of Via Theater. In 1992, Anne founded the SITI Company together with the japanese director Tadashi Suzuki. Her works for SITI Company include: Radio Macbeth; Hotel Cassiopeia; Death and the Ploughman; La Dispute; Score; bobrauschenbergamerica; Room; War of the Worlds; Cabin Pressure; The Radio Play; Alice’s Adventures; Culture of Desire; Bob; Going, Going, Gone; Small Lives/Big Dreams; The Medium; Hay Fever and Private Lives; Miss Julie; and Orestes. She is the author of several books concerning the actor´s craftmanship: A Director Prepares; And Then, You Act and The Viewpoints Book among others.